From Tradition to Transformation: A Scientific Blueprint for Safer Tofu in Bandar Lampung - Subara, Deni; Kumala, Reza; Sylvia, Teny (Journal of Agritechnology and Food Processing, 2025)
Tofu is an affordable, ubiquitous protein source, but its production, especially in small and medium-sized enterprises (SMEs) using traditional methods, presents significant microbiological risks. To address these risks, we analyzed the production process of a local producer, "tahu SMS" in Bandar Lampung, using the Hazard Analysis and Critical Control Point (HACCP) system. Our investigation identified 23 biological, chemical, and physical hazards and established five critical control points (CCPs) at the filtering, coagulation, printing, and packaging stages. The primary outcome is a producer-specific HACCP plan detailing critical limits, monitoring protocols, and corrective actions. This study provides a practical framework for "tahu SMS" to improve food safety and offers a replicable model for integrating scientific safety principles into traditional tofu production